School partnership strategies with business and industry to enhance the employability - Irfan Ahmad; Emay Mastiani (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study analyzes the strategies of Vocational High Schools (SMK) in partnering with the Business and Industrial World (DUDI) through the Plan–Do–Check–Act (PDCA) framework. It responds to the persistent issue of high unemployment among SMK graduates in Indonesia, which reflects a gap between school competencies and industry demands. Using a qualitative comparative case study method, the research explores two institutions with different characteristics: SMKN 1 Karangtengah and SMKN Pertanian Pembangunan (PP) Cianjur. Data were collected through observation, interviews, and document analysis involving principals, vice principals, and industry partners. The findings show that both schools implemented PDCA systematically but with distinct emphases. SMKN 1 Karangtengah pursued large-scale, multi-sectoral partnerships supported by ±80 industrial partners, highlighting programs such as long-term internships, teaching factories, industrial classes, and international networks. In contrast, SMKN PP Cianjur specialized in agribusiness and fisheries, focusing on laboratory-based practices, local industry collaboration, and the Open Day program with Polbangtan. Both schools successfully improved graduate absorption rates, reaching 100% by 2024, yet evaluation still centered more on hard skills than on soft skills. The study concludes that PDCA serves not only as a quality management tool but also as a strategic framework for sustaining vocational partnerships. While SMKN 1 Karangtengah demonstrates the effectiveness of broad-scale networking, SMKN PP Cianjur illustrates the strength of specialization. This comparative analysis highlights that effective partnership strategies must align with institutional capacity, identity, and labor market needs. The study’s novelty lies in presenting a cross-case perspective that identifies replicable best practices for strengthening vocational education partnerships in Indonesia.